Proteolipid Protein Gene Mutation Induces Altered Ventilatory Response to Hypoxia in the Myelin-Deficient Rat - Miller, Martha J. (J Neurosci, 2003)
Pelizaeus Merzbacher disease is an X-linked dysmyelinating disorder of the CNS, resulting from mutations in the proteolipid protein (PLP) gene. An animal model for this disorder, the myelin-deficient (MD) rat, carries a point mutation in thePLP gene and exhibits a phenotype similar to the fatal, connatal disease, including extensive dysmyelination, tremors, ataxia, and death at approximately postnatal day 21 (P21). We postulated that early death might result from disruption of myelinated neural pathways in the caudal brainstem and altered ventilatory response to oxygen deprivation or hypercapnic stimulus. Using barometric plethysmography to measure respiratory function, we found that the MD rat develops lethal hypoxic depression of breathing at P21, but hypercapnic ventilatory response is normal. Histologic examination of the caudal brainstem in the MD rat at this age showed extensive dysmyelination and downregulation of NMDA and to a lesser extent GABA(A)receptors on neurons in the nucleus tractus solitarius, hypoglossal nucleus, and dorsal motor nucleus of the vagus. Unexpectedly, immunoreactive PLP/DM20 was detected in neurons in the caudal brainstem. Not all biosynthetic functions and structural elements were altered in these neurons, because phosphorylated and nonphosphorylated neurofilament and choline acetyltransferase expression were comparable between MD and wild-type rats. These findings suggest that PLP is expressed in neurons in the developing brainstem and thatPLP gene mutation can selectively disrupt central processing of afferent neural input from peripheral chemoreceptors, leaving the central chemosensory system for hypercapnia intact.